Mineral composition and total polyphenol content of polysaccharide-rich extracts from the edible mushroom Auricularia delicata - Alain Tshisuaka Nkongolo; Daddy Kanika Kileshe; Roger Batubenga; Clément Liyongo Inkoto; Gertrude Luswamu Mbumbu; Koto-Te-Nyiwa Ngbolua; Joseph Kasali Lumande; Jeff Bekomo Iteku; Simon Mpulusu Dibaluka (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
This study aimed to evaluate the biopharmaceutical potential of polysaccharides from A. delicata, commonly consumed as an edible mushroom by the populations of Kinshasa and its surroundings. This biopharmaceutical aspect makes the species a functional food and a source for the production of new drugs against several human diseases. The objective of the study is to measure the mineral composition and total polyphenol content present in extracts rich in polysaccharides from A. delicata. These compounds are reported in the literature as having antioxidant and other biological activities. The results obtained confirmed a moderate fraction of the total polyphenol content, detected at an absorbance of 10.256 ± 0.363 mg GAE/g, and mineral elements, of which iron is dominant in higher quantities than the 19 other minerals measured from polysaccharide-rich extracts. The mineral composition and total polyphenol content in polysaccharide-rich extracts of Auricularia delicata show how much the species is a source of functional food (alicament), with medicinal and therapeutic properties. The presence of these compounds (mineral elements and polyphenols) offers hope for the use of A. delicata in the biopharmaceutical field by the populations of Kinshasa and its surroundings, but also provides a basis for the development of biologically active molecules.